Nutritional Quality of Edible Marine Bivalves from the Southern Coast of Italy, Mediterranean Sea - Francesca Biandolino; Antonella Di Leo; Isabella Parlapiano; Loredana Papa; Santina Giandomenico; Lucia Spada; Ermelinda Prato (Polish Journal of Food and Nutrition Sciences, 2019)
Nutritional quality parameters of eight commercially important bivalve species ( Arca noae, Flexopecten glaber, Limaria tuberculata, Mimachlamys varia, Modiolus barbatus, Mytilus galloprovincialis, Ostrea edulis and Solen marginatus ) from the Ionian Sea (Southern Italy, Mediterranean Sea), were determined. The meat yield and lipid nutritional quality indices (atherogenic index, thrombogenicity index and hypocholesterolaemic/hypercholesterolaemic fatty acid ratio) have been also evaluated. Meat yield values ranged from 31.4% in F. glaber to 44.5% in M. varia . The results showed that all species might be considered as food item. Among PUFAs, eicosapentaenoic (EPA) and docosahexaenoic acids (DHA) exhibited highest levels in M. galloprovincialis (11.74%) and in M. varia (14.41%), respectively. Elevated n-3/n-6 ratio characterized the fatty acids profile of all species ranging from 2.65 in F. glaber to 7.19 in M. galloprovincialis . The lipid nutritional quality indices showed that M. varia, M. galloprovincialis, O. edulis, S. marginatus and L. tuberculata might have beneficial effects for the consumer’s health. This paper will be of practical value from a health perspective for populations who consume shellfish and a powerful marketing tool for the bivalves farmer.